Efficacy and safety of oral anticoagulants in the treatment of chronic kidney disease with atrial fibrillation or venous thromboembolism: a systematic review and meta-analysis - Yin, Qinan; Zheng, Xingyue; Ni, Xiaoqing; Wang, Yin; Huang, Xuefei; Song, Yujie; Han, Lizhu; Huang, Youjin; Bian, Yuan (Frontiers in Pharmacology, 2025)
BackgroundThe choice of oral anticoagulants for patients with Chronic Kidney Disease (CKD) combined with venous thromboembolism (VTE) or atrial fibrillation (AF) remains controversial.ObjectiveTo compare the efficacy and safety of warfarin and direct oral anticoagulants (DOACs) in the treatment of CKD with atrial fibrillation or venous thromboembolism.MethodsRelevant publications were sourced from databases like PubMed, Embase, Web of Science, Cochrane Library, and ClinicalTrials.gov up to 30 June 2024. Only RCTs assessing the efficacy and safety of warfarin and DOACs for treating CKD with AF or VTE were included in the meta-analysis. The review outcomes are thrombosis recurrence or VTE-related deaths and major bleeding for CKD patients with VTE, and stroke or systemic embolism and major bleeding for CKD patients with AF. The risk of bias in all included studies was evaluated using the Cochrane Collaboration’s tool.ResultsAfter reviewing 540 studies, 15 randomized controlled trials (RCTs) with 16,361 participants were included. The study found that DOACs reduced the risk of hemorrhagic stroke compared to warfarin in patients with AF and CKD (RR = 0.455, 95% CI: 0.275–0.752, P = 0.002). There was no significant difference in ischemic stroke incidence between the two. DOACs also lowered the risk of major bleeding in patients with AF and CKD compared to warfarin (RR = 0.604, 95% CI: 0.442–0.825, P = 0.002), and significantly reduced the risk of intracranial bleeding (RR = 0.424, 95% CI: 0.287–0.626, P < 0.001). All five studies reported recurrent VTE or VTE-related deaths, showing no significant difference between warfarin and DOAC groups (RR = 0.663, 95% CI: 0.409–1.073, P = 0.094), Patients with renal dysfunction on either treatment had similar risks of major bleeding events (RR = 0.543, 95% CI: 0.209–1.407, P = 0.208).ConclusionDOACs demonstrate superior efficacy and safety compared to warfarin in patients with AF and CKD. Additionally, DOACs exhibit comparable efficacy and safety to warfarin in patients with VTE and CKD.Systematic Review Registrationhttp://www.clinicaltrials.gov, identifier (CRD42024510727).